Training in minimally invasive surgery in urology: European Association of Urology/International Consultation of Urological Diseases consultation. (14th October 2015) - van der Poel, Henk; Brinkman, Willem; van Cleynenbreugel, Ben; Kallidonis, Panagiotis; Stolzenburg, Jens‐Uwe; Liatsikos, Evangelos; Ahmed, Kamran; Brunckhorst, Oliver; Khan, Mohammed Shamim; Do, Minh; Ganzer, Roman; Murphy, Declan G.; et al.
Abstract : Objectives: To describe the progress being made in training for minimally invasive surgery (MIS) in urology. Methods: A group of experts in the field provided input to agree on recommendations for MIS training. A literature search was carried out to identify studies on MIS training, both in general and specifically for urological procedures. Results: The literature search showed the rapidly developing options for e‐learning, box and virtual training, and suggested that box training is a relatively cheap and effective means of improving laparoscopic skills. Development of non‐technical skills is an integral part of surgical skills training and should be included in training curricula. The application of modular training in surgical procedures showed more rapid skills acquisition. Training curricula for MIS in urology are being developed in both the USA and Europe. Conclusion: Training in MIS has shifted from 'see‐one‐do‐one‐teach‐one' to a structured learning, from e‐learning to skills laboratory and modular training settings.